1993
DOI: 10.1002/smi.2460090105
|View full text |Cite
|
Sign up to set email alerts
|

General versus specific measures of occupational stress: An Australian police survey

Abstract: Groups of police officers from two Australian police forces completed a number of psychological tests to determine the stressors of police life and to assess the impact of a number of personality variables on stress appraisals. Work stresses were found to fall into two discernible categories: job content stressors — those which arise from the duties police officers carry out — and job context stressors — those which derive from the nature of the police organizations in which officers perform their duties. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
7

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 31 publications
3
48
0
7
Order By: Relevance
“…La existencia de estudios basados en conceptualizaciones de contexto de trabajo con algunos elementos diferenciadores a los de este estudio presentan, entre otros, como factores estresantes más frecuentes de dicho contexto los siguientes: trabajar horas extras y la falta de apoyo (11), fracasar en el curso del entrenamiento, fracasar en los exámenes de promoción y tener una evaluación personal insatisfactoria (12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La existencia de estudios basados en conceptualizaciones de contexto de trabajo con algunos elementos diferenciadores a los de este estudio presentan, entre otros, como factores estresantes más frecuentes de dicho contexto los siguientes: trabajar horas extras y la falta de apoyo (11), fracasar en el curso del entrenamiento, fracasar en los exámenes de promoción y tener una evaluación personal insatisfactoria (12).…”
Section: Discussionunclassified
“…La influencia del contexto del trabajo en la salud ha venido investigándose en diferentes profesiones como enfermería (6-8; trabajadores sociales (9), agentes de policía (10)(11)(12), y sectores empresariales diversos como: servicios, enseñanza, sanidad/ farmacia, industria (13), industria petrolífera en alta mar (14), construcción (15) …”
Section: Introductionunclassified
“…Although some aspects of the work environment may be shared by many occupations, others may be specific to certain occupations, and even specific workplaces (Trenberth and Dewe, 2006), and standardized questionnaires fail to identify issues deriving from actual work duties (Evans and Coman, 1993): For example, influence over the length and composition of the postal route may be a critical feature for postal workers, yet would not be picked up by standardized measures of working conditions. In a qualitative study, Dewe (1989) concluded that globalized measures do not lead to a better understanding of the nature and structure of, for example, actual problems in the workplace.…”
Section: Methodological Challenges In Using Standardized Questionnairmentioning
confidence: 99%
“…Muitos estudos encontraram que os policiais não apresentam comportamentos de adaptação e enfrentamento adequados (Burke, 1994;Evans & Coman, 1993;Graf, 1986;McCafferty e colaboradores, 1992;Richmond, Wodak, Kehoe & Heather, 1998). Richmond e colaboradores (1998) encontraram um consumo excessivo de álcool entre os policiais, tendo sido relatados altos índices de divórcio e suicídio como um tipo de fracasso ao enfrentamento (Evans & Coman, 1993;McCafferty e cols, 1992).…”
Section: Discussão E Conclusõesunclassified
“…Richmond e colaboradores (1998) encontraram um consumo excessivo de álcool entre os policiais, tendo sido relatados altos índices de divórcio e suicídio como um tipo de fracasso ao enfrentamento (Evans & Coman, 1993;McCafferty e cols, 1992). A esse respeito, Graf (1986), em sua amostra, verificou que dois terços dos policiais civis raramente lidam com os desagrados de seu trabalho e não se sentem confiantes de suas habilidades em lidar com os mesmos.…”
Section: Discussão E Conclusõesunclassified